(untitled) (Bioscience Journal, 2021)
Several studies have suggested that athletes with disabilities experience more difficulties having access to oral health care than the population in general. The aim of this study was to estimate the impact of socio-demographic/socio-economic factors, oral hygiene habits and clinical oral health conditions on the OHRQoL – Oral Health-Related Quality of Life (assessed with the Oral Health Impact Profile 14 – OHIP-14) on a sample of athletes with heterogeneous types of disabilities. Altogether, 105 athletes with disabilities were evaluated. Cross-sectional data was collected including interviews to obtain socio-demographic/socio-economic data, the OHIP-14 and clinical oral examinations parameters. The outcome variable was the OHIP-14 severity score. The explanatory variables were sex, age, monthly household income, level of schooling, frequency of toothbrushing and flossing, gingival bleeding, periodontal disease, trauma in incisors, prosthesis wearing and needs, number of sound teeth, DFMT (decayed, filled and missing teeth) index and its isolate components. Mann-Whitney, Kruskall-Wallis and Spearman tests used to compare OHIP-14 severity scores associated with the explanatory variables. The mean OHIP-14 severity score for the sample was 9.32 (SD 8.99) and the most affected domain was Physical Pain (mean 2.63; SD 1.97), followed by Psychological Discomfort (mean 1.81; SD 2.02). Significant differences in mean OHIP-14 scores were found for periodontal disease, need for complete dentures, number of sound teeth, DFMT index and its components. These results suggest that these clinical parameters can be related to impaired OHRQoL for this population.